The histone H2B Arg95 residue efficiently recruits the transcription factor Spt16 to mediate Ste5 expression of the pheromone response pathway - Abdallah Alhaj Sulaiman (17777421) (2023)
In yeast Saccharomyces cerevisiae, the immunosuppressant rapamycin inhibits the TORC1 kinase causing rapid alteration in gene expression and leading to G1 arrest. We recently reported the isolation and characterization from the histone mutant collection of a histone H2B R95A mutant that displays resistance to rapamycin. This mutant is defective in the expression of several genes belonging to the pheromone response pathway including STE5 encoding a scaffold protein that promotes the activation of downstream MAP kinases. Cells lacking Ste5 cannot arrest the cell cycle in response to rapamycin and as a consequence exhibit similar resistance to rapamycin as the H2B R95A mutant. Herein, we show that the H2B R95A mutation weakens the association of H2B with Spt16 a component of the FACT complex (FAcilitates Chromatin Transcription), and an essential factor that interacts with the histone H2A-H2B dimer to promote transcription and preserve chromatin integrity. From a collection of spt16 mutants, spt16 E857K and spt16-11 showed striking sensitivity to rapamycin as compared to the parent strain. spt16 E857K and spt16-11 expressed distinct forms of Ste5, while a suppressor mutation H2B A84D of the spt16-11 mutant prevents the expression of Ste5 and confers marked resistance to rapamycin. We interpret these findings to suggest that the Arg95 residue of histone H2B is required to recruit Spt16 to maintain the expression of STE5, which performs a role to arrest cells in the G1 phase in response to rapamycin. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-023-37339-y